The Paralinguistic Nonverbal Communication Style of Teacher at RA Baiturrohim - Erlina Putri Andayani; Eny Nur Aisyah; Rosyi Damayani Twinsari Maningtyas (Ceria: Jurnal Program Studi Pendidikan Anak Usia Dini, 2026)
This study aims to describe the teacher’s paralinguistic nonverbal communication style and its impact on children’s learning engagement at RA Baiturrohim, Lowokwaru, Malang City. The topic was chosen because paralinguistic communication plays an essential role in early childhood learning, where children respond more naturally to intonation, facial expressions, and gestures than to verbal explanations. This research employed a qualitative descriptive approach with 1 class B teacher and 16 children aged 5-6 as subjects. Data were collected through observation, interviews, and documentation. The findings show that the teacher consistently used varied intonation, situation-adjusted volume, and calm speech frequency to support children’s understanding. Cheerful facial expressions and active gestures strengthened verbal messages and created a lively classroom atmosphere. Children were observed to be more focused, responsive, and engaged when the teacher combined vocal cue with expressive body movement. The study concludes that paralinguistic nonverbal communication not only clarifies instructional messages but also fosters emotional connection, ensures a sense of security, and naturally enhances children’s learning engagement.